2007
DOI: 10.1016/j.ejcts.2007.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord perfusion after extensive segmental artery sacrifice: can paraplegia be prevented?

Abstract: Interruption of all SAs at 32 degrees C in this pig model results in a spectrum of cord injury, with normal function in a majority of pigs postoperatively. The short duration of low SCPP suggests that hemodynamic manipulation lasting only 24-48h may allow routine complete preservation of normal cord function despite sacrifice of all SAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 21 publications
5
55
0
2
Order By: Relevance
“…Fortunately, we did not observe spinal ischemia in this series. Additionally, experimental and clinical data support the hypothesis, that spinal ischemia is mainly induced by prolonged periods of systemic hypotension and not by the number of patent intercostals arteries [14,15]. Finally, cerebrospinal fluid drainage during and within the first 72 h after stent-graft placement may serve as a valuable adjunct in avoiding this serious adverse event [16].…”
Section: Commentmentioning
confidence: 91%
“…Fortunately, we did not observe spinal ischemia in this series. Additionally, experimental and clinical data support the hypothesis, that spinal ischemia is mainly induced by prolonged periods of systemic hypotension and not by the number of patent intercostals arteries [14,15]. Finally, cerebrospinal fluid drainage during and within the first 72 h after stent-graft placement may serve as a valuable adjunct in avoiding this serious adverse event [16].…”
Section: Commentmentioning
confidence: 91%
“…Experimental studies have demonstrated that the collateral network undergoes remodelling after extensive segmental artery sacrifice with an increase in the diameter of the spinal artery within 24 h and further enlargement by nearly 100% within 5 days [19]. Similarly, the pressure measured in the distal stump of the sacrificed segmental artery shows a nadir several hours postoperatively, increases to 60% of preoperative levels by 48 h and recovers to preoperative values at 5 days [20].…”
Section: Discussionmentioning
confidence: 98%
“…Against the longstanding doctrine that the major spinal cord blood-supplying vessel is located at the thoraco-abdominal transition, experimental and clinical work have shown that the spinal cord blood supply is supported by a complex network of several contributing major vascular territories [13][14][15].…”
Section: Discussionmentioning
confidence: 99%